Efficacy and Safety of First‐Line Chemotherapy With Gemcitabine Plus Nab‐Paclitaxel in Unresectable Gallbladder Cancer - Yue Yang; Ziyou Wu; Yidi Zhu; Yu Zhang; Zhe Zhou; Xiaoling Song; Ziyi Yang; Shilei Liu; Runfa Bao; Xuefeng Wang; Xiangsong Wu; Wei Gong (Cancer Medicine, 2026)
ABSTRACT Purpose The purpose of this study is to evaluate the efficacy and safety of nab‐paclitaxel combined with gemcitabine (AG regimen) as a first‐line chemotherapy for patients with unresectable gallbladder cancer (GBC). Materials and Methods A retrospective analysis was conducted on patients diagnosed with GBC via histological examination. Inclusion criteria included locally advanced or metastatic gallbladder cancer deemed unresectable by multidisciplinary team (MDT) consensus; age 18–75 years; ECOG performance status ≤ 2; and AG as first‐line chemotherapy. Treatment response was assessed using RECIST 1.1 criteria. Primary endpoints were overall response rate (ORR) and progression‐free survival (PFS); secondary endpoints included disease control rate (DCR), overall survival (OS), and adverse events incidence. Results Thirty‐one patients were enrolled. The ORR was 48.4%, and DCR was 90.3%. The median PFS was 8.4 months (95% CI, 5.0–11.8), and the median OS was 20.9 months (95% CI, 16.8–24.9). Among the 11 patients with locally advanced disease, 7 patients (63.6%) successfully converted to a resectable state and underwent surgery. Grade 3/4 treatment‐related adverse events occurred in 11 patients (35.5%), predominantly hematologic toxicities, and no treatment‐related deaths or treatment discontinuations due to adverse events were observed. Conclusion First‐line AG chemotherapy demonstrated promising efficacy and manageable safety for patients with unresectable GBC, with a substantial portion achieving disease control and some converting to resectable status.